Epidemiology of Non-Communicable Diseases Associated with Exposure to Radiation: Research Results and Future Directions - V. K. Ivanov (Эпидемиология и вакцинопрофилактика, 2019)
Relevance.  The circulatory  system  diseases  (CSD) are the leading cause of peoples’  death globally.  Therefore  the assessment of radiation risk of mortality for CSD is the most important task for radiation epidemiology, especially in low dose range (below 1 Gy). Aim: to establish the relationship between circulatory diseases incidence among the Chernobyl emergency accident workers (liquidators) and radiation dose they got. Materials and methods.  The object under study is the cohort of liquidators with known individual doses of external gamma exposure of whole body. The group of potential risk is identified by values of excess relative risk (ERR) and relative risk (RR) estimated in the cohort of 134 thousand people, the average radiation dose is 0.11 Gy, maximum individual dose is about 1 Gy. For the period of follow up from 1986 through 2012 12400 deaths were caused by CSD. Results. The group of potential radiation risk comprises of the liquidators with accumulated doses 0.15 Gy and above, they arrived in the Chernobyl exclusion zone in the first year after the accident and stayed there less than 6 weeks. The total size of the identified group was 9.5 thousand people (7% of the cohort members). In the group of potential radiation risk the statistically significant value of RR is 1.44 (95% CI: 1.25; 1.66), averageaccumulated dose is 0.23 Gy. In this risk group 31% of deaths from CSD should be considered as associated with radiation. In the beginning of 2013 the size of the group of potential radiation risk was 6155 liquidators. Conclusions. For remained life about 950 radiation induced deaths from CSD are expected. Adherence of liquidators of the risk group to prevention and control of circulatory system diseases would significantly decrease years of life lost due to radiation exposure in this cohort.